The Effect of Edmodo-Based Project Based Learning on Students' Critical Thinking Skills: Meta-analysis - Bucky Wibawa Karya Guna; Abdullah Ardi; Khaerudin Khaerudin; Bachtiar Nasution; Andri Kurniawan; Jumadi Nur; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect of project-based learning edmodo on students' critical thinking skills. This is a meta-analysis. Data sources come from 11 national and international journals published in 2019-2024. The process of searching for data sources through the databases of google scholar, ERIC, ScienceDirect, Researchgate and Taylor of Francis. Search keywords are learning through edmodo, Project Based Learning, Etnomodo based project based learning, and the influence of edmodo based project based learning on students' critical thinking skills. Data selection through PRISMA 2020 method. Analyze data with SAP applications. The results of the study concluded that the application of project-based learning edmodo had a significant effect on students' critical thinking skills with an average effect size value of 1.03 with high criteria. This finding shows that project-based learning edmodo has a positive influence on improving students' critical thinking skills in schools.